POTENSI AKTIVITAS ANTIOKSIDAN BIJI ADAS (Foeniculum vulgare Mill) SEBAGAI PENANGKAP RADIKAL BEBAS - Suhendra, Lutfi; Arnata, I Wayan (Universitas Udayana, 2009)
Target of this research was to obtain solvent type, toobtain ability on antiradical, and to find out optimumconcentration of extract powder of fennel seed. This researchconsisted of two phases that the first phase wasdetermination of total phenol and antioxidant activity usingTBA method at various solvent type. Solvent used forextraction was ethanol and acetate ethyl. The concentrationsof the solvent were 0, 15, 30, 45, 60, 75 and 90%.Antioxidant activity resulted from each variation of type andconcentration of solvent was used for the examination in thesecond phase in determining antiradical activity by DPPH.Variation of concentration of fennel extract was 100, 250,500, 750 and 1000 ?g/ml yielded from type of ethano l andacetate acid solvents.Obtained data of each treatment was plotted in a graph.Data validity was analized using appropriate regressionanalysis on plotted data in graph. Result of research indicatedthat antioxidant active compound extracted using acetateethyl solvent was higher than that using ethanol solvent.Optimum concentration of extract of fennel powder fromethanol and acetate ethyl solvent in scavenging free radicalwas 975 ppm and 850 ppm.